2014
DOI: 10.1016/j.mce.2014.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of human adipocytes implicates the NOD-like receptor pathway in obesity-induced adipose inflammation

Abstract: Adipose tissue inflammation increases with obesity, but adipocyte vs. immune cell contributions are unclear. In the present study, transcriptome analyses were performed on highly-purified subcutaneous adipocytes from lean and obese women, and differentially expressed genes/pathways were determined in both adipocyte and stromal vascular fraction (SVF) samples. Adipocyte but not SVF expression of NOD-like receptor pathway genes, including NLRP3 and PYCARD, which regulate caspase-1-mediated IL-1β secretion, corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 44 publications
(55 reference statements)
3
82
1
1
Order By: Relevance
“…Furthermore, a reduction in the secretion of insulin-sensitive adipokines accompanied by oversecretion of proinflammatory cytokines (TNF-α, IL-1β, and IL-6) is closely related to the etiology of various metabolic conditions. Other studies also point to the participation of NLRP3 in obesity because of its overexpression in AT [11,[69][70][71][72][73]. Moreover, the results of studies on mouse models of obesity are consistent with this observation [74,75].…”
Section: Obesity and T2dsupporting
confidence: 60%
“…Furthermore, a reduction in the secretion of insulin-sensitive adipokines accompanied by oversecretion of proinflammatory cytokines (TNF-α, IL-1β, and IL-6) is closely related to the etiology of various metabolic conditions. Other studies also point to the participation of NLRP3 in obesity because of its overexpression in AT [11,[69][70][71][72][73]. Moreover, the results of studies on mouse models of obesity are consistent with this observation [74,75].…”
Section: Obesity and T2dsupporting
confidence: 60%
“…Other groups showed that saturated fatty acid-induced inflammation causes mitochondrial impairment in adipocytes, while saturated fatty acids can upregulate NLRP3 inflammasome activation (38, 39). Also, a higher level of NLRP3 inflammasome components were detected in obese patients, and active caspase-1 were increased with obesity development in adipose tissues (40). Interestingly, caspase-1 deficient mice gained less weight and they had less adipose tissue formation in the HFD-induced obesity mouse model (41).…”
Section: Nlrp3 Inflammasome In Disease; Metabolic Disordermentioning
confidence: 97%
“…The expression of human NLRP3 and ASC/PYCARD is upregulated in adipocytes from obese patients 119 . Caspase-1 expression was found in both human and mouse adipose tissues and increases with adipocyte differentiation and obesity development 120 .…”
Section: Inflammasomes In Diseasementioning
confidence: 99%